Driving factors behind Indonesia’s 2015 decision to cooperate with Malaysia in CPOPC: Economic, political, and environmental considerations - Nashiir, Mohammad; Krisnamukti, Tedy Asjad (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2025)
Indonesia’s palm oil industry, a cornerstone of national economic growth and rural livelihoods, faced escalating trade barriers and sustainability demands, particularly from the European Union, from 2005 to 2015. This study investigates Driving factors behind Indonesia’s 2015 decision to cooperate with Malaysia in CPOPC: Economic, political, and environmental considerations, using employing Richard C. Snyder’s foreign policy decision-making framework to systematically analyze the interplay of internal and external factors. The research adopts a qualitative explanatory literature review, synthesizing data from peer-reviewed journals, policy documents, and credible news sources published from 2005 to 2015. The analysis reveals that Indonesia’s policy shift was driven by the convergence of domestic economic imperatives such as maintaining export revenues, supporting smallholders, and responding to industry lobbying, and mounting external pressures including discriminatory European Union regulations, NGO campaigns, and global market competition. The formation of CPOPC is shown to be a pragmatic diplomatic response, enhancing Indonesia’s bargaining power, promoting sustainable palm oil standards, and fostering collective action with Malaysia to counter external challenges. This research fills a gap in the literature by demonstrating how multi-level decision-making processes and transnational alliances can be mobilized to safeguard national interests in contested global commodity markets. The findings offer practical insights for policymakers and industry stakeholders on the importance of strategic cooperation and adaptive diplomacy in the face of evolving international trade and sustainability regimes.